The Application of Waqf and Endowment Fund Based on the Principles in the Sharia Maqashid Pillar Society - Akhmad Kusuma Wardhana (Prosperity)
Islam regulates economic life for the benefit of all. Waqf can be a solution in creating mutual benefit in society. This study aims to analyze the comparison between the practice of waqf for both Muslims and non-Muslims. This study uses qualitative methods. Samples in this study are the Islamic Hospital of endowments and the Gates Foundation. Data were analyzed using descriptive-analytical methods. The results show that the Gates Foundation and UNISMA use funds from their business management to distribute to the public. If UNISMA distributes waqf funds for business development and to achieve goodness, the gates foundation is entirely donated to the public. The difference in the company's financial scale is this division.